2019
DOI: 10.4103/ijem.ijem_646_18
|View full text |Cite
|
Sign up to set email alerts
|

Drug prescription patterns and cost analysis of diabetes therapy in India: Audit of an endocrine practice

Abstract: Aims: The aim of this study was to analyze the current trend in the use of antidiabetes as well as other drugs for comorbidities along the duration of diabetes. The study also aimed to analyze the direct drug cost to patients. Settings and Design: Retrospective cross-sectional study. Subjects and Methods: Data captured in clinic electronic medical records of an endocrine practice was analyzed. Statistical Analysis Used: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 15 publications
3
46
0
Order By: Relevance
“…The mean age of the persons with diabetes was around 54 years with majority of individuals in the 40–65 age groups, which is comparable to earlier similar studies in different parts of India [ 13 14 , 16 17 ] and significantly lower ( P < 0.0000001) than a study conducted in the northeastern state of Sikkim. [ 15 ] This age is also significantly lower than that seen in the U.S. and other countries [ 18 19 20 ] indicating an earlier age of onset of T2DM in our setting.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The mean age of the persons with diabetes was around 54 years with majority of individuals in the 40–65 age groups, which is comparable to earlier similar studies in different parts of India [ 13 14 , 16 17 ] and significantly lower ( P < 0.0000001) than a study conducted in the northeastern state of Sikkim. [ 15 ] This age is also significantly lower than that seen in the U.S. and other countries [ 18 19 20 ] indicating an earlier age of onset of T2DM in our setting.…”
Section: Discussionsupporting
confidence: 84%
“…[ 7 ] The mean duration of diagnosed diabetes was more than 8 years, which is statistically similar to earlier reported data. [ 14 15 ] Patients are likely to come to a tertiary care center later in their diabetes progression; almost half the patients had a duration of diabetes of >5 years which is a significantly higher proportion compared to a recently published from a private center in New Delhi, [ 13 ] and one fourth had duration >10 years.…”
Section: Discussionmentioning
confidence: 99%
“…[16] We reported previously that 44% of people with diabetes were prescribed vitamin supplements during their routine diabetes care. [19] Secondly, people without diabetes might seek attention later due to long latent period of manifestations of vitamin B12 deficiency. Our effort to document exogenous supplementation was not successful due to non-centralized nature of healthcare system in India and over-the-counter availability of vitamin B12 preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfonylureas (SUs) are widely used in India because of their glucose-lowering efficacy and affordability, with glimepiride and gliclazide being the most commonly prescribed SUs. A retrospective cross-sectional study from India found an increase in the use of SUs from 23.12% in patients with diabetes for 0–5 years to 70.77% in patients with diabetes for 10–15 years [ 3 ].…”
Section: Introductionmentioning
confidence: 99%